PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR IPAS MATERI PERISTIWA ALAM PADA MURID KELAS V SDN 22 SALONGGE - Nuraing Nuraing; Dian Firdiani; Dedi Setiawan (STKIP Subang, 2026)
NURAING. 2026. Application of the Problem Based Learning Model to Improve Science Learning Outcomes on Natural Events Material for Fifth Grade Students of SDN 22 Salongge, Baraka District. Supervisor I: Dr. Dian Firdiani, S.Pd., M.Pd. and Supervisor II: Dedi Setiawan, S.Pd., M.Pd. This study aimed to determine the effectiveness of the Problem Based Learning (PBL) model in improving science learning outcomes on natural events material among fifth-grade students of SDN 22 Salongge. The research employed Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The subjects of this study were 15 students. Data were collected through observation, tests, and documentation and analyzed using quantitative descriptive techniques. The findings revealed that the implementation of the Problem Based Learning model significantly improved students’ learning outcomes. The average score increased from 71.33 in the pre-action stage to 80.67 in Cycle I and further improved to 91.33 in Cycle II. In addition, the percentage of students achieving learning mastery increased from 67% in the pre-action stage to 80% in Cycle I and reached 100% in Cycle II. These results indicate that the Problem Based Learning model is effective in enhancing students’ understanding and learning outcomes in science, particularly on natural events material for fifth-grade students of SDN 22 Salongge.